Design, Management and Innovation - de Oliveira, André Ribeiro; Monat, André Soares; da Silva Jr, Dércio Santiago; Zöhrer, Pedro; Spiegel, Thais (DAT Journal, 2024)
This article addresses the historical foundations of industrial design, exploring the development of design from the division of labor in factories to the consolidation of design as a scientific discipline that has formalized traditional areas such as product and service design. Emphasis is placed on the importance of sustainability in design and the holistic approach that, by considering the life cycle of products and services, integrates innovation management and entrepreneurship as a means to guide design practices within institutions. The dialogue between design and management is systematized through a methodological approach known as design science, which aims to bridge theory and practice, seeking solutions applicable to the real world. Finally, the text discusses the strategic importance of design, aligning project vision with the long-term objectives of institutions, and integrating operational, tactical, and strategic dimensions. The impact of Generative Artificial Intelligence (GAI) on contemporary design is also highlighted, illustrating how these technologies are transforming the creative process.